Perbandingan Penerapan Algoritma A*, IDA*, Jump Point Search, dan PEA* P ada Permainan Pacman - Rosa Delima; Gregorius Titis Indrajaya; Abednego Kristiawan Takaredase; Ignatia Dhian E.K.R.; Antonius Rachmat C (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Pathfinding is a way to find the shortest route between two points. There are several A* variant algorithms such as Iterative Deepening A* (IDA*) algorithm, Partial Expansion A* (PEA*), and Jump Point Search (JPS). In this research, the writer evaluates the performance of A*, IDA* algorithm, JPS, and PEA* algorithm. The algorithms are implemented in pacman game and the writer get the data by measuring visited nodes, and the route it takes.  Based  on the  analysis  of  algorithms  in  a  game,  it concluded that  the algorithms  have  the  same  path solution, but JPS algorithm has less visited nodes than A*, IDA*, and PEA*